2020
DOI: 10.1111/1462-2920.14987
|View full text |Cite
|
Sign up to set email alerts
|

QuiC2 represents a functionally distinct class of dehydroshikimate dehydratases identified in Listeria species including Listeria monocytogenes

Abstract: Summary Many Listeria species including L. monocytogenes contain the pathway for the biosynthesis of protocatechuate from shikimate and quinate. The qui1 and qui2 operons within these Listeria spp. encode enzymes for this pathway. The diversion of shikimate pathway intermediates in some Listeria species to produce protocatechuate suggests an important biological role for this compound to these organisms. A total of seven ORFs, including quiC2, were identified within qui1 and qui2, however only three proteins e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…MG1655 ∆ aroE strain used in this study did not contain any modifications enhancing aromatic pathway. At the same time, recent studies showed that catabolic DSDs are highly diverse and it is possible that more advanced enzymes will be found [ 40 , 41 ]…”
Section: Discussionmentioning
confidence: 99%
“…MG1655 ∆ aroE strain used in this study did not contain any modifications enhancing aromatic pathway. At the same time, recent studies showed that catabolic DSDs are highly diverse and it is possible that more advanced enzymes will be found [ 40 , 41 ]…”
Section: Discussionmentioning
confidence: 99%